Book review “Manuel Balado, sus aportes a la construcción de la neurocirugía argentina” - Campero, Abraham Agustín (Revista Argentina de Neurocirugía, 2024)
The book Manuel Balado. Sus aportes a la construcción de la neurocirugía argentina, written by Mezzadri and Picard, highlights his fundamental role in the development of neurosurgery in Argentina and Latin America. Manuel Balado stood out for his contributions in neuroanatomy and electrophysiology, introducing techniques such as iodoventriculography. His research on the innervation of the iris, published in 1927, is an example of his scientific rigor. As founder of the “Archives of Neurology” and editor of the Zentralblatt für Neurochirurgie, he contributed to the dissemination of knowledge in the region. In addition to his scientific work, Balado was an outstanding teacher, training numerous generations of neurosurgeons. This biography is a valuable document that highlights the figure of a pioneer who laid the foundations of neurosurgery in South America.